Peningkatan Kompetensi Bermain Drama dengan Metode Lavonte - Widiastuti, Yuanita; Arrozaq, M. Fadlulloh; Ambarwati, Ari (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2022)
Drama performances performed by students of class XI SMA have a lack of self-confidence, to overcome this the researcher applies the Lavonte method, namely vocal exercises, and expression therapy. This study aims to make students of class XI MIPA 1 SMAN 1 Kraksaan able to improve their competence in expressing the dialogue of the characters in drama performances using the Lavonte method. The sample of this study consisted of 32 students. Indonesian language subject, basic competence "Expressing Dialogue of Characters in Drama Performance", semester 2, 2019-2020 school year. Data were collected through questionnaires, observation notes and evaluation results from the beginning of the study until the second cycle. Observation notes are used to determine the increase in the competence of students in expressing the dialogues of the characters in drama performances, while the evaluation is carried out to measure the increase in student achievement. The results showed that the lavender method could be used to improve students' competence in expressing the dialogues of the characters in drama performances. The increase in student competence can be seen in the quality of the process shown by the seriousness, courage, and concentration of students in the learning process and practice to create a pleasant atmosphere. Students also do not feel bored because the activities in the lavender method vary. The assessment of the results of drama practice is seen in four aspects, namely intonation, pronunciation, appreciation, and expression. The highest score for each aspect is 4, while the total score for all aspects is 20. The process and product improvement can be seen based on the average score obtained in the second cycle compared to the average score obtained during the first cycle. The practice average score of students in the first cycle of 10.01. The average score of student practice at the end of the second cycle is 14.55. So, there was an increase in the average score of students by 4.54 or 45.35%. This increase in score indicates that the implementation of the actions in cycle I and cycle II can increase students' competence in expressing the dialogues of the characters in drama performances.Â AbstrakPementasan drama yang dilakukan oleh peserta didik kelas XI SMA memiliki kendala kekurangaan percaya diri, untuk menanggulanginyaÂ  peneliti menerapkan metode lavonte yakni latihan vokal dan terapi ekspresi. Penelitian ini bertujuan agar siswa kelas XI MIPA 1 SMAN 1 Kraksaan dapat meningkatkan kompetensi mengekspresikan dialog para tokoh dalam pementasan drama dengan metode lavonte. Sampel penelitian ini ber jumlah peserta didik 32 anak. Mata pelajaran bahasa Indonesia, kompetensi dasar â€Mengekspresikan Dialog Para Tokoh dalam Pementasan Dramaâ€, semester 2, tahun pelajaran 2019-2020. Â Data yang dikumpulkan melalui angket, catatan observasi dan hasil evaluasi yang dilakukan sejak awal penelitian sampai siklus II. Catatan observasi dipergunakan untuk mengetahui peningkatan kompetensi peserta didik dalam mengekspresikan dialog para tokoh dalam pementasan drama, sedangkan evaluasi dilakukan untuk mengukur peningkatan prestasi belajar peserta didik. Hasil penelitian menunjukkan bahwa metode lavonte dapat digunakan untuk meningkatkan kompetensi siswa dalam mengekspresikan dialog para tokoh dalam pementasan drama. Peningkatan kompetensi siswa tersebut tampak pada kualitas proses yang ditunjukkan oleh keseriusan, keberanian, dan konsentrasi siswa dalam proses pembelajaran dan praktik sehingga dapat menciptakan suasana yang menyenangkan. Siswa juga tidak merasa bosan karena dalam kegiatan dalam metode lavonte bervariasi. Penilaian hasil praktik drama dilihat dalam empat aspek yaitu intonasi, pelafalan, penghayatan, dan ekspresi. Nilai tertinggi setiap aspek adalah 4, sedangkan nilai total semua aspek adalah 20. Peningkatan secara proses dan produk dapat dilihat berdasarkan skor rata-rata yang diperoleh pada siklus II dibandingkan dengan skor rata-rata yang diperoleh pada saat siklus I. Skor rata-rata praktik siswa pada siklus I sebesar 10,01. Skor rata-rata praktik siswa di akhir siklus II sebesar 14,55. Jadi, terjadiÂ  peningkatan skor rata-rataÂ  siswa sebesar 4,54 atau 45,35%. Peningkatan skor ini menunjukkan bahwa implementasi tindakan dalam siklus I dan siklus II mampu meningkatkan kompetensi siswa dalam mengekspresikan dialog para tokoh dalam pementasan drama.